Clinical strategy to enhance cyclic fatigue resistance of Ni-Ti rotary files using refrigerant spray. - Punnarai, Panitnart; Morakul, Sarita; Pongakaragul, Prasert; Panitvisai, Piyanee; Hiran-us, Sirawut (BMC Oral Health, 2025)
Background: The cyclic fatigue resistance of nickel–titanium (NiTi) rotary files can be improved by lowering their temperature. However, previously proposed methods for reducing file temperature have not been clinically practical. This study investigated the effect of refrigerant spray on the cyclic fatigue resistance and fractographic characteristics of various NiTi rotary files, considering both alloy type and motion pattern. Methods: Twenty NiTi rotary files from each brand—ProTaper Universal (PTU), ProTaper Next (PTN), ProTaper Gold (PTG), Reciproc (REC), Reciproc Blue (REB), and WaveOne Gold (WOG)—were randomly allocated to sprayed and non-sprayed groups (n = 10 each). In the experimental groups, Endo-Frost spray was applied for 10 s, whereas control groups received no spray. File temperatures were measured immediately after spraying with a thermocouple before cyclic fatigue testing. All instruments were operated in a 60° curved stainless steel canal with a 5-mm radius at 37 °C until fracture. The time to fracture (TTF) and fractured fragment length (FL) were recorded. Data were analyzed using t-tests for TTF and FL within each system and one-way ANOVA for temperature comparisons across groups. Fractured files were subsequently examined under a dental operating microscope (DOM) and a scanning electron microscope (SEM) for fractographic evaluation. Results: Mean TTF values were significantly higher in the spray-applied groups compared with the controls (p < 0.001). No significant differences were observed in FL or in file temperature across groups. All samples exhibited features of cyclic fatigue failure under both DOM and SEM examination. Fractographic analysis revealed distinct fracture patterns between sprayed and non-sprayed groups, as well as among different alloys. Conclusions: Refrigerant spray was associated with increased cyclic fatigue resistance in all tested rotary files, regardless of alloy or motion.